Sztuczna inteligencja i roboty wyzwaniem dla prawa - Maj, Magdalena (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2019)
The aim of the article was to analyze the impact of artificial intelligence and robots on the law. The author presented how new technologies related to the transhumanist trend. The article also includes an answer how artificial intelligence can help lawyers and which countries regulate the sphere of robots and artificial intelligence.
Keywords: robots; new technologies; robotics; artificial intelligence; transhumanism